Conservationists' perspectives on poverty: An empirical study. Issue 3 (3rd June 2020) - Fisher, Janet A.; Dhungana, Hari; Duffy, Janine; He, Jun; Inturias, Mirna; Lehmann, Ina; Martin, Adrian; Mwayafu, David M.; Rodríguez, Iokiñe; Schneider, Helen
Abstract: Biodiversity conservation interventions have long confronted challenges of human poverty. The ethical foundations of international conservation, including conservation's relationship with poverty, are currently being interrogated in animated debates about the future of conservation. However, while some commentary exists, empirical analysis of conservation practitioner perspectives on poverty, and their ethical justification, has been lacking thus far. We used Q methodology complemented by more detailed qualitative analysis to examine empirically perspectives on poverty and conservation within the conservation movement, and compare these empirical discourses to positions within the literature. We sampled conservation practitioners in western headquartered organizations, and in Bolivia, China, Nepal and Uganda, thereby giving indications of these perspectives in Latin America, Asia and Africa. While there are some elements of consensus, for instance the principle that the poor should not shoulder the costs of conserving a global public good, the three elicited discourses diverge in a number of ways. Anthropocentrism and ecocentrism differentiate the perspectives, but beyond this, there are two distinct framings of poverty which conservation practitioners variously adhere to. The first prioritizes welfare, needs and sufficientarianism, and is more strongly associated with the China, Nepal and Uganda case studies. The second framing of poverty focuses much more on the need for 'do no harm' principles and safeguards, and follows an internationalized human rights‐oriented discourse. There are also important distinctions between discourses about whether poverty is characterized as a driver of degradation, or more emphasis is placed on overconsumption and affluence in perpetuating conservation threats. This dimension particularly illuminates shifts in thinking in the 30 or so years since the Brundtland report, and reflecting new global realities. This analysis serves to update, parse and clarify differing perspectives on poverty within the conservation, and broader environmental movement, to illuminate consensual aspects between perspectives, and reveal where critical differences remain. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article